2020
DOI: 10.1158/0008-5472.can-20-0600
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Enhances the Antitumor Activity of the Glutaminase Inhibitor CB-839 against PIK3CA-Mutant Colorectal Cancers

Abstract: PIK3CA encodes the p110α catalytic subunit of PI3K and is frequently mutated in human cancers, including ∼30% of colorectal cancer. Oncogenic mutations in PIK3CA render colorectal cancers more dependent on glutamine. Here we report that the glutaminase inhibitor CB-839 preferentially inhibits xenograft growth of PIK3CA-mutant, but not wild-type (WT), colorectal cancers. Moreover, the combination of CB-839 and 5-fluorouracil (5-FU) induces PIK3CA-mutant tumor regression in xenograft models. CB-839 treatment inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 45 publications
1
61
1
Order By: Relevance
“…Supportively, Zhao et al reported that combination of CB-839 and 5-fluorouracil induced PIK3CA-mutant tumor regression in CRC xenograft models (148). Importantly, an exploratory analysis of a phase I clinical trial (NCT02861300) showed a trend of better response to combination therapy of CB-839 plus capecitabine (prodrug of 5-fluorouracil) in PIK3CAmutant CRC patients as compared to PIK3CA-WT cohort (148). More data are needed to evaluate the efficiency of glutaminase inhibition in clinical scenarios.…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…Supportively, Zhao et al reported that combination of CB-839 and 5-fluorouracil induced PIK3CA-mutant tumor regression in CRC xenograft models (148). Importantly, an exploratory analysis of a phase I clinical trial (NCT02861300) showed a trend of better response to combination therapy of CB-839 plus capecitabine (prodrug of 5-fluorouracil) in PIK3CAmutant CRC patients as compared to PIK3CA-WT cohort (148). More data are needed to evaluate the efficiency of glutaminase inhibition in clinical scenarios.…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 97%
“…Nevertheless, results of CANTATA (NCT03428217) showed encouraging clinical activity and tolerability of combination therapy of CB-839 plus cabozantinib in metastatic renal cell cancer (147). Supportively, Zhao et al reported that combination of CB-839 and 5-fluorouracil induced PIK3CA-mutant tumor regression in CRC xenograft models (148). Importantly, an exploratory analysis of a phase I clinical trial (NCT02861300) showed a trend of better response to combination therapy of CB-839 plus capecitabine (prodrug of 5-fluorouracil) in PIK3CAmutant CRC patients as compared to PIK3CA-WT cohort (148).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…The combination of the novel GLS inhibitor CB839 with the EGFR monoclonal antibody Cetuximab showed efficacy in Cetuximab-sensitive and -resistant CRC cell models, indicating that patients with refractory metastatic CRC might benefit from this combination therapy targeting both the "fuel" and signaling components required for tumor survival [267]. Additionally, the anti-tumor activity of CB839 in xenograft growth of PIK3CA-mutant CRC cells was enhanced by chemotherapeutic agent 5-fluorouracil without obvious dose-limiting toxicity, indicating the potential of the combination therapy for patients with PIK3CA-mutant colorectal cancer [268].…”
Section: Glutaminolysis Inhibitormentioning
confidence: 99%
“…These include telaglenastat (CB-839) [ 14 ] and bis-2-(5-phenylacetamido-1,3,4-thiadiazol-2-yl) ethyl sulfide (BPTES) [ 13 ]. The antitumor activity of CB-839 is potentiated upon combining with conventional chemotherapeutic agents [ 15 ] and vice versa [ 16 ], suggesting the possibility of glutaminase inhibition as a novel therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%